The Relationship between Abusive Supervision and Proactivity Performance through the Mediator's Role in Goal Orientation: An Analytical Study of the Opinions of a Sample of Faculty Members of the Colleges of Al-Qadisiyah University (Czech Journal of Multidisciplinary Innovations, 2024)
The study looked at the variable of abusive supervision, which is defined as the use of supervisory authority in the context of management in ways that are unlawful or unfair by going beyond the proper bounds of authority and applying it arbitrarily to the people under supervision, as well as the connection between these behaviors and proactive employee performance. The mediating function of the variable of employee goal orientation of all kinds was also covered in the study. (306) university professors from Al-Qadisiyah University's 18 colleges provided their opinions for the study, which used a descriptive analytical approach. The three orientations were towards the goals of learning, proving performance, and avoiding performance. Measures for the three variables used in earlier studies were included in the questionnaire form that was used for data collection in this study. The research findings indicate that there is a statistically significant and indirect relationship between abusive supervision and the proactive performance behavior dimensions of problem prevention, individual voice, individual creativity, and tolerance. accountability) The variables of arbitrary supervision and the aspects of proactive performance behavior under the goal orientation's (orientation towards the goal of proving performance) dimension were found to have an indirect effect relationship that was both direct and statistically significant through the two types of employee goal orientations, which are represented by (orientation towards the learning goal and orientation towards the goal of proving performance). The study's recommendations and proposals, which include the need for Iraqi universities to give careful consideration to the quality of supervision and its influence on academic performance, align with the workers' goals. By enhancing management techniques, it would be possible to lessen the detrimental effects of arbitrary supervision and increase academics' proactive performance, which would raise the bar for scientific research and advance Iraq's academic system